When the Sun Sings Science, Are Children Left in the Dark? Representations of Science in Children's Television and Their Effects on Children's Learning. - Bonus, James Alex; Mares, Marie-Louise (Human Communication Research, 2018)
How is educational information presented in children's science television shows, and how well do preschool viewers learn that information? A content analysis of 21 science programs for children (Study 1) found that half of the examined episodes taught science concepts by introducing and subsequently refuting inaccurate ideas (e.g. clouds are made of cotton candy), and one-third depicted focal science concepts in anthropomorphic ways. An experiment (Study 2) tested the effects of exposure to such representations on preschoolers' science knowledge (N = 78). Despite existing concerns that refutation narratives might unintentionally teach children scientific misconceptions, no such degradations in knowledge occurred. However, children also showed no increases in factual knowledge (relative to a pre-test and to a no-exposure control group). In contrast, children exhibited more factual knowledge after watching episodes that contained anthropomorphic depictions of focal science concepts (relative to a pre-test and to the control group). Implications for existing theory are discussed.